Chinese FrameNet and OWL Representation - Liping You; Tao Liu; Kaiying Liu (Sixth International Conference on Advanced Language Processing and Web Information Technology (ALPIT 2007), 2007)
The Chinese FrameNet Project is creating an lexical resource for Chinese, based on the principles of Frame Semantics and supported by corpus evidence. Our description of each lexical item identifies the frames which underlie a given meaning and the ways in which the Frame Elements are realized in structures headed by the word, through manual annotation of example sentences and automatic summarization of the resulting annotations. It will be available in XML, and can be displayed and queried via the web and other interfaces. We are trying to translate the CFN data into the OWL Web Ontology Language, a revision of the DAML+OIL web ontology language, which can represent our ontologies and to make CFN information machine readable and understandable. This paper reports on our representation of this data in OWL.
Keywords: Chinese FrameNet OWL Chinese lexical resource